Technico-tactical elements of the game as a factor of success in the 2nd European Baskin Cup - Živan Milošević (Exercise and Quality of Life)
The purpose of this research was to examine the effects of certain technico-tactical elements of the Baskin game as a predictor of the achieved result in the 2nd European Cup matches. The following variables were analyzed: number of balls brought to the side basket, saved balls by role 2, saved balls by other roles, three-point shots by role 2, scored points from the corner by the role 2, role 2 misses, number of points by roled 1-5. The Mann-Whitney test was used to evaluate the differences in relation to the outcome of the match (win, loss) and certain technico-tactical elements. The obtained results indicate statistically significant differences between the winning and losing teams in fourteen analyzed games for points scored from the points scored by players with role 3.